In the absence of ATPase activity, pre-RC formation is blocked prior to MCM2–7 hexamer dimerization - Evrin, Cecile (Oxford University Press, 2013)
The origin recognition complex (ORC) of Saccharomyces cerevisiae binds origin DNA and cooperates with Cdc6 and Cdt1 to load the replicative helicase MCM2–7 onto DNA. Helicase loading involves two MCM2–7 hexamers that assemble into a double hexamer around double-stranded DNA. This reaction requires ORC and Cdc6 ATPase activity, but it is unknown how these proteins control MCM2–7 double hexamer formation. We demonstrate that mutations in Cdc6 sensor-2 and Walker A motifs, which are predicted to affect ATP binding, influence the ORC–Cdc6 interaction and MCM2–7 recruitment. In contrast, a Cdc6 sensor-1 mutant affects MCM2–7 loading and Cdt1 release, similar as a Cdc6 Walker B ATPase mutant. Moreover, we show that Orc1 ATP hydrolysis is not involved in helicase loading or in releasing ORC from loaded MCM2–7. To determine whether Cdc6 regulates MCM2–7 double hexamer formation, we analysed complex assembly. We discovered that inhibition of Cdc6 ATPase restricts MCM2–7 association with origin DNA to a single hexamer, while active Cdc6 ATPase promotes recruitment of two MCM2–7 hexamer to origin DNA. Our findings illustrate how conserved Cdc6 AAA+ motifs modulate MCM2–7 recruitment, show that ATPase activity is required for MCM2–7 hexamer dimerization and demonstrate that MCM2–7 hexamers are recruited to origins in a consecutive process.